Black Swans in ecology and evolution: The importance of improbable but highly influential events - Nuñez, Martin Andres (2012)
The role of improbable but highly influential events in ecology and evolution is poorly understood. Recent works in economics and finance emphasize the importance that these events, so-called Black Swans, can have for the behavior, predictability and ultimately understanding of complex economic systems. Ecology and evolution are also complex systems that involve the interaction of organisms with their environment in different time scales and therefore they should also experience Black Swans. Here, we briefly discuss the nature of Black Swans, and their potential role in ecology and evolution. Traditionally, ecological and evolutionary research has been mostly focused in normal or regular events, while rare events have been usually ignored. However, several highly consequential events in ecology and evolution could qualify as Black Swans. For example, the sudden emergence of a new deadly pathogen, or, the rapid extinction or diversification of a lineage could be considered Black Swans. Thus, including the Black Swan phenomenon in ecological and evolutionary thinking may be necessary for a better understanding of these subjects.